How collaborative mental health care for competitive and high-performance athletes is implemented: A novel interdisciplinary case study - Van Slingerland, Krista J.; DesClouds, Poppy; Durand-Bush, Natalie; Boudreault, Véronique; Abraham, Anna (Frontiers in Psychology, 2022)
Collaborative care is considered a best practice in mental health care delivery (Bullock et al., 2017) and has recently been applied in high-performance sport to address athletes’ mental health needs (Moesch et al., 2018; Van Slingerland and Durand-Bush, 2021). However, how the collaborative process unfolds in practice in the sport setting has not yet been well documented. The purpose of this illustrative case study was to investigate a novel interdisciplinary approach used within the CCMHS to provide mental health care to clients. Focusing on ‘how’ the approach was implemented, the study provides insight into the collaboration that occurred between mental performance and mental health practitioners to provide care to a high-performance athlete over an 11-month period, as well as factors facilitating and impeding the team’s collaboration. The case involved three practitioners and a 16-year-old female athlete experiencing chronic pain, low mood, and elevated anxiety. In the first phase of the data collection process, each practitioner engaged in guided reflective journaling (Yinger and Clark, 1981) to describe the case and reflect on their practice and outcomes. During the second phase, practitioners co-created a case timeline to describe the collaborative process using clinical documents (Bowen, 2009). Lastly, practitioners participated in collaborative reflection (Collin and Karsenti, 2011) to collectively reflect more broadly on collaboration practice occurring within the CCMHS and Canadian sport system. The data depict a complex care process in which the necessity and intensity of collaboration was primarily driven by the client’s symptoms and needs. A content analysis showed that collaboration was facilitated by the CCMHS’ secure online platform and tools, as well as individual practitioner and team characteristics. Collaboration was, however, hindered by logistical challenges, overlapping scopes of practice, and client characteristics. Overall, there were more perceived benefits than drawbacks to providing collaborative care. While flexibility was required during the process, deliberate and systematic planning helped to ensure success.